What proportion of couples with a history of recurrent pregnancy loss and with a balanced rearrangement in one parent can potentially be identified through cell-free DNA genotyping? - Laura J. C. M. van Zutven; Jona Mijalkovic; Monique van Veghel-Plandsoen; Margaret Goense; Marike Polak; Maarten F. C. M. Knapen; Sabina de Weerd; Marieke Joosten; Karin E. M. Diderich; Lies H. Hoefsloot; Diane Van Opstal; Malgorzata I. Srebniak (Molecular Cytogenetics, 2023)
Abstract Background Balanced chromosome aberrations are reported in about 1:30 couples with recurrent pregnancy loss (RPL). Karyotyping of both parents is necessary to identify these aberrations. Genome-wide non-invasive prenatal testing (NIPT) in case of recurrent pregnancy loss could be a more efficient way to identify couples at increased risk for carrying a balanced chromosome rearrangement. The aim of this study was to evaluate whether the potential fetal imbalances caused by parental balanced aberrations detected in our center are large enough to be detectable by genome-wide non-invasive prenatal testing (NIPT). Material and methods From January 1970 until May 2020 our laboratory received 30,863 unique requests for karyotyping due to RPL. We have identified 16,045 couples and evaluated all abnormal cytogenetic results to assess the minimal size of the involved chromosomal segments in potential unbalanced products of the rearrangements. Results In the presented cohort we detected 277 aberrant balanced translocations/inversions in females and 185 in males amongst 16,045 couples with RPL, which can be translated to a risk of 1:35 (2.9%, 95% CI 2.6–3.2%). Our study showed that the vast majority (98.7%, 95% CI 97.1–99.5%) of these balanced aberrations will potentially cause a fetal imbalance > 10 Mb, which is detectable with genome-wide NIPT if it was performed during one of the miscarriages. Conclusions Our study suggests that genome-wide NIPT is able to reveal most unbalanced products of balanced chromosomal rearrangements carried by couples with RPL and therefore can potentially identify balanced chromosomal aberration carriers. Moreover, our data suggest that these couples can be offered NIPT in case they decline invasive testing in future pregnancies.